Lymph node evaluation during combination treatment of rectal cancer - Grzela, Monika; Windorbska, Wiesława; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2005)
Lymph node status is the strongest predictor of tumor recurrence and overall survival for patients with colorectal cancer and is associated with the increased use of adjuvant treatment. The International Union Against Cancer requires at least 12 negative nodes in a surgical specimen to be present to confirm adequate staging in node negative patients. The percentage of patients with lymph node involvement has been shown to increase with the number of lymph nodes recovered. The impact of preoperative radiotherapy on pathologic lymph node evaluation has not yet been quantified. The purpose of this study was to analyse the number of recovered lymph nodes in the surgical specimen in 120 patients treated in the Cancer Center in Bydgoszcz from 1999 to 2004 and to review the literature. Patients underwent short-term preoperative radiotherapy (5x5 Gy, 5 days) and surgical treatment within 7 days after radiotherapy. The number of lymph nodes recovered and the number of positive lymph nodes were abstracted from patients’ pathology reports. The median number of lymph nodes examined was 8 (0-29). Only 28 (23.33%) patients had 12 or more lymph nodes examined and 6 (5%) patients had no lymph nodes recovered from the surgical specimen. In a group of 57 pN0-patients only 8 (14.04%) had more than 12 lymph nodes examined, 13 (22.81%) had 10-12 lymph nodes examined and 6 (10.53%) had no lymph nodes recovered from the surgical specimen. A few rectal cancer patients underwent adequate lymph node staging. Additional research is crucial to evaluate the effect of lymph node staging on the outcome for rectal cancer patients who undergo preoperative radiotherapy.